Toward a feminist ethics of nonviolence - Cavarero, Adriana; Butler, Judith, 1956-; Honig, Bonnie; Guaraldo, Olivia; Battersby, Christine, 1946-; Bernini, Lorenzo, 1973-; Devenney, Mark, 1968-; Forti, Simona (Fordham University Press, 2021)
"Toward a Feminist Ethics of Nonviolence brings together three major feminist thinkers to discuss Cavarero's call for a postural ethics of nonviolence. The book consists of three longer essays by Cavarero, Judith Butler, and Bonnie Honig, followed by shorter responses by a range of scholars that widen the dialogue, drawing on post-Marxism, Italian feminism, and queer theory. Together, the authors contest the boundaries of their common project for a pluralistic, heterogeneous, but urgently feminist ethics of nonviolence."--Back cover.